A STUDY ON COMPARISON BETWEEN THE DIALECTS OF WEST SIMEULUE AND MIDDLE SIMEULUE - Sariakin (Getsempena English Education Journal, 2016)
This study is about a comparative study between the dialect of West Simeule and Middle Simeulu. The aim of this study is to find out the differences between the dialects of west Simeulue and middle Simeulue.The subject of this study is all of the utterances of West Simeulue and Middle Simeulue dialects. While the sample of the study is taken from twenty adult informants who are native speakers form the two dialects. The data needed are collected through interview. Meanwhile the data gotten are analyzed by describing the difference between dialects which are used by people of West Simeulu and Middle Simuelu. The result of the study shows that there are three different dialects that are used in West Simeulu and Middle Simeulu; differences in morphology, differences in preposition, differences in vocabulary.